Self-Respect Movement in Tamil Nadu, 1920-1940 - Mangalamurugesan, N. K. (Nataraja Kandasamy), 1946- (Koodal Publishers, 1979)
Social reform movements in Tamil Nadu during 1920-40, with reference to Self-Respect Movement founded by E.V. Ramaswami Naicker, Tamil rationalist and sociopolitical activist.